Powerful Community Relationships and Union Renewal in Australia - Tattersall, Amanda (Relations industrielles / Industrial Relations, 2006)
Terms such as labour-community coalitions, community unionism and social movement unionism are important features of current strategies for union renewal. This article develops a three-part framework of union-community relationships, from ad hoc to deeply engaged relationships. Criteria such as common interest, coalition structure, scale and union participation are identified as important variables for relationship variation and campaign success. The article explores the framework by analyzing three case studies from Sydney, Australia, involving the central labour council—Unions NSW. The paper argues that union-community relationships vary significantly; ad hoc relationships are useful to react to a crisis while deeper relationships are most useful to build a long-term agenda. Deeper relationships are supported when they are built alongside a process of internal union renewal. Deeper relationships are more successful if unions develop workplace leaders, support political union education and provide space for workplace stewards to connect to community campaigns.